The moderating role of ceos' political connection on the relationship between corporate governance mechanisms and firm performance among listed companies in Palestine - Saleh, Mohammed W. A. (2019)
Corporate Governance (CG) issues are now the core subject for business leaders and regulators worldwide. Since Palestinian listed firms on Palestine Securities Exchange (PSE) have experienced a weak performance due to the poor governance, focusing on the relationship between corporate governance and performance of Palestinian firms contributes to the literature. Using the frameworks of agency theory, resource dependence theory and busyness hypothesis, this study examined the relationship of board characteristics, Audit Committee (AC) characteristics, Chief Executive Officer (CEO) characteristics and ownership structures on firm performance. It also examined the role of CEO Political Connection (PC) in the relationship between CG mechanisms and performance of Palestinian firms over the period 2009 to 2016. Mixed method approach was used in the study. The study used 200 firm-year observations from the annual reports of firms listed in PSE. Besides, series of semi-structured interviews were conducted with the board members, CEO, Chief Financial Officer (CFO) and shareholders to ensure the robustness of the quantitative findings. Panel data regressions were used on the quantitative data to examine the effect of the predictors on performance. The results showed that board financial knowledge, AC meeting, AC financial expertise and CEO tenure were positively associated with performance. Conversely, board size, board independence, CEO multiple directorships, and institutional ownership were negatively associated with performance. Moreover, it was established that CEO PC strengthens the relationship between AC meeting, AC financial expertise, family ownership and performance. However, the CEO PC weakens the relationship between board size, board financial knowledge, foreign directors, AC size, CEO tenure, director ownership and performance. This study provided various theoretical implications such as exposing how CEO multiple directorships can negatively affect the firm’s performance. Regulators may use the findings of the study to upgrade the existing code to improve CG practices, especially in the Palestinian perspective.